Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Aparatur Dinas Pendidikan dan Kebudayaan Kota Gorontalo - Arifah Rizqina Wanaartha Rauf; Sri Yulianty Mozin; Yacob Noho Nani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Education and Culture Office of Gorontalo City as a Regional Apparatus (PD) that manages government functions in the education and culture sector. Through the performance achievement assessment, it is known that the planned quality standards have not been fully achieved in accordance with the set targets. This study aims to determine whether Organizational Culture has a partial effect on the Performance of Apparatus in the Education and Culture Office of Gorontalo City, whether the Work Environment has a partial effect on the Performance of Apparatus in the Education and Culture Office of Gorontalo City, whether Organizational Culture and Work Environment simultaneously affect the Performance of Apparatus in the Education and Culture Office of Gorontalo City. This study uses a quantitative method with a population of 91 people. Data collection techniques are carried out through questionnaires, observation and documentation. Data analysis uses the help of SPSS software version 21. The results of the study explain that Organizational Culture has a positive effect on the performance of the Education and Culture Office of Gorontalo City with a partial determination coefficient of 26.70%. The work environment has a positive effect on the Performance of the Education and Culture Office of Gorontalo City with a partial determination coefficient of 43.80%. Organizational culture and work environment jointly influence the performance of the Gorontalo City Education and Culture Office apparatus with a simultaneous determination coefficient of 70.50%.